MANGROVE COMMUNITY STRUCTURE AT MANGROVE ECOTOURISM AREA IN KAYU ARA PERMAI VILLAGE, SIAK REGENCY - Tika Nisari; Muhammad Fauzi; Ridwan Manda Putra (Berkala Perikanan Terubuk, 2021)
This research was conducted on July - August, 2020 in mangrove ecotourism area ofKampung Kayu Ara Permai, Siak Regency. The purpose of this study was to obtain thevalue of density, frequency, mangrove important value index (INP Mangrove),dominance index value and mangrove diversity index in the mangrove ecotourism areaof Kampung Kayu Ara Permai. Five serial plots with provisions of 10x10 meters2 for 2trees, 5x5 meters for shrubs, and 2x2 meters2 for seedlings. Each plot identified species, measured stem diameter, and the number of individual mangroves. Vegetation analysisusing Mueller and Dumbois formulas to get the value of diversity, frequency, dominanceand importance of plants. The results showed that nine species of mangrove vegetationwere found: Avicennia alba, Avicennia marina, Bruguiera gymnoriza, Bruguierasexangula, Bruguiera sylindrica, Lumnitzera littorea, Rhizophora apiculata, Rhizophoramucronata, and Rhizophora stylosa. The highest importance index was found inRhizophora apiculata (102.4%). Mangrove diversity in this area is high (5.28) and isdominated by Rhizophora apiculata. The high diversity of mangroves is due to thepreservation of this area by community groups.